Efficacy and Safety of Canagliflozin in Individuals Aged 75 and Older with Type 2 Diabetes Mellitus: A Pooled Analysis. Issue 3 (March 2016) - Sinclair, Alan J.; Bode, Bruce; Harris, Stewart; Vijapurkar, Ujjwala; Shaw, Wayne; Desai, Mehul; Meininger, Gary
Abstract : Objectives: To compare the efficacy and safety of canagliflozin, a sodium glucose co‐transporter 2 inhibitor developed to treat type 2 diabetes mellitus (T2DM), in individuals younger than 75 and those aged 75 and older. Design: Randomized Phase 3 studies. Setting: International study centers. Participants: Adults with T2DM. Measurements: Changes from baseline in glycosylated hemoglobin (HbA1c ), fasting plasma glucose (FPG), blood pressure (BP), and body weight were measured. Efficacy was evaluated using pooled data from six randomized, double‐blind, placebo‐controlled studies (N = 4, 158; n = 3, 975 aged <75, n = 183 aged ≥75). Safety was assessed based on adverse event (AE) reports from eight randomized, double‐blind, placebo‐ and active‐controlled studies (N = 9, 439; n = 8, 949 aged <75, n = 490 aged ≥75). Results: Canagliflozin 100 and 300 mg were associated with placebo‐subtracted mean reductions in HbA1c in participants younger than 75 (−0.69% and −0.85%, respectively) and aged 75 and older (−0.65% and −0.55%, respectively). Dose‐related reductions in FPG, body weight, and BP were seen with canagliflozin 100 and 300 mg in participants in both age groups. Overall AE incidence was 67.1% with canagliflozin 100 mg, 68.6% with canagliflozin 300 mg, and 65.9% with non‐canagliflozin (pooled group of comparators in all studies) in participants younger than 75, and 72.4%, 79.1%, and 72.3%, respectively, in those aged 75 and older, with a similar safety profile in both groups. The incidence of volume depletion–related AEs was 2.2%, 3.1%, and 1.4% in participants younger than 75 with canagliflozin 100 and 300 mg and non‐canagliflozin, respectively, and 4.9%, 8.7%, and 2.6%, respectively, in those aged 75 and older. Conclusion: Canagliflozin improved glycemic control, body weight, and BP in participants aged 75 and older. The overall incidence of AEs was high across treatment groups in participants aged 75 and older and higher than in those younger than 75. The safety profile of canagliflozin was generally similar in both age groups, with a higher incidence of AEs related to volume depletion observed with canagliflozin in participants aged 75 and older than in those younger than 75. These findings support canagliflozin, starting with the 100‐mg dose, as an effective therapeutic option for older adults with T2DM.